Pengaruh Right Issue terhadap Respon Investor Yang Dimoderasi oleh Pandemi Covid-19 pada Sub Sektor Perbankan di Bursa Efek Indonesia - Varajna Ayu Tejalengkara; Juniarti Juniarti (Business Accounting Review, 2021)
This study aims to determine how investors respond to rights issues during the COVID-19 pandemic in the banking sub-sector on the Indonesia Stock Exchange. The independent variable in this study is the right issue, and the dependent variable in this study is the investor's response which researchers measured using cumulative abnormal return. This study also uses three control variables: leverage, firm size, and market share. In addition, the covid-19 pandemic in this study is a moderator of the relationship between the rights issue and investor response. The sample in this study is the banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2021 period, selected using purposive sampling and obtained as many as 112 companies. The data analysis technique of this research is panel data regression, with the chosen estimation model, the Common Effect Model (CEM). The results obtained indicate that the rights issue does not affect the cumulative abnormal return. But, the COVID-19 pandemic moderates the relationship between rights issues and cumulative abnormal returns. Even though researchers conducted a comparative test, it did not yield any results.